PENGARUH WORK FROM HOME DAN INDEPENDENSI TERHADAP KUALITAS AUDIT INTERNAL APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH KOTA MANADO SELAMA MASA PANDEMI (STUDI EMPIRIS PADA INSPEKTORAT KOTA MANADO) - Butarbutar, Tarida Elisa; Pesak, Pricilia Joice (Universitas Sam Ratulangi, 2021)
The outbreak of the Corona virus or COVID-19 has not only rocked Wuhan, but also the world. The coronavirus pandemic has caused many large institutions and banks to decide to change their forecasts for global economic conditions. In Indonesia, the corona virus spreads very quickly, resulting in a crisis in various fields, the most felt is the economy. In the economic field, COVID-19 has had such an extraordinary impact, one of which is in the audit process. The audit process, which is usually carried out offline or face to face to check the company's finances and performance for a period of one year, must be carried out online or remotely due to the COVID-19 situation. This makes internal auditors as examiners and supervisors of financial statements need to Work optimally. This study aims to analyze and prove empirically the effect of Work From Home and independence on the quality of internal audit of the inspectorate apparatus in regional financial supervision. This type of research is quantitative research, using primary data through questionnaires Respondents in the study were internal supervisory officers working on the Inspectorate of Manado City. The sample used was 50 respondents, who were directly involved in the inspection activities. The data were analyzed using multiple linear regression analysis and data testing was carried out with the help of the SPSS version 22 program. The results showed that: 1). Work from home has a significant positive effect on the quality of the internal audit of the inspectorate apparatus in the regional financial supervision of Manado City. 2). Independence has a significant positive effect on the quality of the internal audit of the inspectorate apparatus in the regional financial supervision of Manado City.